The two-dimensional cutting stock problem with usable leftovers and uncertainty in demand - Nascimento, Douglas Nogueira [UNESP]; Cherri, Adriana Cristina [UNESP]; Oliveira, José Fernando; Oliveira, Beatriz Brito (Elsevier, 2023)
When dealing with cutting problems, the generation of usable leftovers proved to be a good strategy for decreasing material waste. Focusing on practical applications, the main challenge in the implementation of this strategy is planning the cutting process to produce leftovers with a high probability of future use without complete information about the demand for any ordered items. We addressed the two-dimensional cutting stock with usable leftovers and uncertainty in demand, a complex and relevant problem recurring in companies due to the unpredictable occurrence of customer orders. To deal with this problem, a two-stage formulation that approximates the uncertain demand by a finite set of possible scenarios was proposed. Also, we proposed a matheuristic to support decision-makers by providing good-quality solutions in reduced time. The results obtained from the computational experiments using instances from the literature allowed us to verify the matheuristic performance, demonstrating that it can be an efficient tool if applied to real-life situations.
Keywords: Matheuristic; Stochastic problem; Two-dimensional cutting stock problem; Uncertainty in demand; Usable leftovers